Mi’kmaq / Non-Mi’kmaq Conversational Turn-Taking - Inglis, Stephanie (Engaged Scholar Journal, 2021)
Turn-taking during verbal interactions is a linguistic and cultural pattern that regulates who is to speak during a conversation and when. Conversational turn-taking includes the length of time that occurs after the speaker says something and before the person spoken to responds (Ryan & Forrest, 2019). Within the academy at this current time of 2020, diverse knowledge holders, both Indigenous and Non-Indigenous, are actively trying to share and merge knowledge epistemologies across culture and across language. Though sharing is now actively taking place much more frequently between these two groups of scholars within Canadian universities, full comprehension of what is being communicated is not always realized by both parties. This is not due to any fault on the researchers’ part, but because many times two turn-taking paradigms are being used in a conversation instead of one.